Allelopathic effect of leaf leachates of solid bamboo Dendrocalamus stocksii (Munro.) on growth and yield of Eleusine coracana L. (Gaertn.) - Rawat, Pravin; Narkhede, S.S.; Rane, A.D.; Mhaiske, V.M.; Dalvi, V.V. (Indian Journal of Agroforestry, 2020)
An experiment was carried out to assess allelopathic effect of leaf leachates of solid bamboo Dendrocalamus stocksii (Munro.)Â onÂ growth and yield of finger millet (Eleusine coracana). Bamboo leaf leachate was prepared by soaking dry leaves in tap water for 24 hours in a ratio of 1:10 (w/v). Using this as stock solution, various concentrations (25, 50 and 75%) were prepared. The results revealed concentration-dependent inhibitory effect of bamboo leaf leachates on the germination, radicle and plumule length of finger millet. The leachate of mild concentration (25%) had an exceptionally stimulatory effect on radicle length in laboratory conditions. In pot culture experiment, concentration-dependent stimulatory effect of all the leaf leachates was observed on the number of tillers per plant and straw yield ha-1. Higher concentrations of 75 and 100% stimulated the seed yield per plant and grain yield ha-1 as compared to the control treatment. It is concluded that the harmful effect of leaf leachates of D. stocksii is more prominent in early growth stage (germination, emergence of radicle and plumule) and it is recommended to avoid the effect of these allelochemicals in early growth stage.